EFFECT OF WATER SPRAY AND FORMALDEHYDE TREATED AND UNTREATED ANISE SEEDS UNTREATED ANISE SEEDS SUPPLEMENTATION ON P PHYSIOLOGICAL PERFORMANCE OF HOLSTEIN COWS UNDER H HEAT STRESS - Shwayel, Mohammed A.; Saleh, Natik H. (Diyala Agricultural Sciences Journal, 2015)
This study was carried out at the Animal Farm pertaining to the Department of Animal Resources, College of Agriculture, University of Baghdad, using 18 multiparous Holstein cows following their beak milk production. The cows were randomly divided into two main groups (with and without spraying the body with water). Each group was sub-divided into three sub groups including 3 cows each representing treatment of anise (0 and 30 gm of formaldehyde- treated anise as well as 30 gm. Formaldehyde untreated anise to the concentrate diet/cow/day). The field part of the experiment was continued for the period from 1/7/2012 to 2/10/2012 to study the effect these treatments on the productive and physiological performance under heat stress conditions in Summer. Results revealed that the experimental cows were exist under severe heat stress during the experiment which negatively affected on some studied traits. The highest temperature-humidity index (THI) was 85.05 during the fourth week of July. The cow's average daily milk yield (DMY) was 11.97 kg. Evening rectal temperature was decreased (P< 0.05) as influenced of treated and non-treated anise in 1/8/ 2012 namely 38.55 and 38.51º C respectively, while being 39.00º C for control group. On the other hand, the evening average respiratory rate was decreased (P < 0.05) for the 30gm anise –formaldehyde treated group in 1/8/2012 namely 41.66 respiration/minute in comparison with the control group (42.33 respiration/minute). In 1/9/2012 a significant (P < 0.05) decreases in evening average respiratory rate was observed for treated and untreated anise groups namely 38.66 respiration/minute as compared with the control group (45.83 respiration/minute) till the end of the experiment. The water spraying decreased (P <0.05) average rectal temperature, respiratory and pulse rates in 1/8/2012 namely 38.37 º C, 38.00 and 61.55 once/minute in comparison with non-sprayed group 39.00º C, 46.66 and 64.77 once/minute respectively and till the end of the experiment. The interaction between the anise and water spraying was positively significant on most studied traits.